Metode Al-Hira' Dalam Meningkatkan Keterampilan Membaca Al-Qur’an Mahasiswa STIT Payakumbuh - Elsa Sepputri; Ali Nasuha (Journal of Education and Social Culture, 2025)
It turns out that reading the Qur'an for students of Islamic Religious Education at Payakumbuh Tarbiyah College of Science is still a difficult matter, as a result they are wrong in reading the Al-Quran, even though they are prospective Islamic Religion teachers, who cannot be separated from the arguments of Al-Qur'an. Koran. Therefore, in this study the Al-Hira method was applied which can improve Al-Qur'an reading in these students. The novelty of this method is that it is very practical in learning to read the Koran, starting from simple things to difficult things, so that it is easy for students or the general public to do. The approach taken by researchers is a qualitative approach. After the researchers carried out the Al-Quran reading test twice, the first test showed that one person was not fluent in reading. In the second test of the 21 test takers, all of them were fluent in reading the Qur'an.